Marios Varvoglis, Alekos Xenos, Mikis Theodorakis: Three Musical Approaches to Greek Revolution on Stage - Kalopana, Magdalini (Ariadne, 2026)
Three stage productions by the National Theatre of Greece that reference the Greek Revolution reveal the institution’s theatrical approach to the national narrative from the early 20th century to its final quarter: To Live the Messolonghi by Vassilis Rotas, directed by Fotos Politis, with incidental music by Marios Varvoglis (1933); Rigas Velestinlis by Spyros Melas, directed by Alexis Minotis, with music by Alekos Xenos (1962); and Kapodistrias by Nikos Kazantzakis, directed by Alexis Solomos, with music by Mikis Theodorakis (1976). Focusing on incidental music, the stylistic and ideological orientation of each composer reflects the prevailing official interpretation of national identity during each corresponding period—namely, the interwar years, the post-civil war era of national reconciliation, and the metapolitefsi (“regime change”). Socio-cultural aspects of these productions are examined through historical and musical references, shedding light on the evolving trajectory from national consciousness to Greekness within the context of modern Greek art music.